Anthropological Measurement of the Juvenile Clavicle Using Multi‐Detector Computed Tomography—Affirming Reliability. Issue 4 (17th May 2013) - Brough, Alison L.; Bennett, Jonathan; Morgan, Bruno; Black, Sue; Rutty, Guy N.
Abstract Currently, there is no standardized protocol for multi‐detector computed tomography (MDCT) measurement of juvenile remains. Using 33 juvenile clavicles, this paper investigates a protocol to allow MDCT measurements, comparable or supplemental with traditional osteometric measurements, to be acquired for application to previously published algorithms. The results illustrate that there is no significant difference between MDCT measurements and those taken by direct osteometric methods. By presenting such a protocol, this paper takes the first steps toward validation of the process of conversion from measurement of dry juvenile bone to MDCT compatibility and allows the forensic world to take a step forward in standardizing the way MDCT is used for forensic practice. This paper assesses the limitations and potential applications of this virtual approach and offers some suggestions for where further work might progress the conversion of these new approaches into legally admissible anthropological techniques of age estimation.